Survival status and predictors of mortality from severe community-acquired pneumonia among under-five children admitted at Debre Tabor comprehensive specialized hospital: a prospective cohort study - Kassaw, Amare; Kerebih, Gashaw; Zeleke, Shegaw; Chanie, Ermias Sisay; Dessalegn, Nigatu; Bante, Berihun; Teshome, Asefa Ageghehu; Chekole, Bogale; Gelaw, Belete; Bayih, Wubet Alebachew; Tesfaw, Aragaw; Feleke, Dejen Getaneh; et al. (Frontiers in Pediatrics, 2023)
Background: Pneumonia continues to be the biggest killer of under-five years aged children globally. Ethiopia ranks fourth with the highest death rate of under-five mortality due to severe community acquired pneumonia (SCAP) among 15 countries worldwide. However, to this date there is no recent study that shows survival status and predictors of mortality from SCAP. Therefore, this study was aimed to determine survival status and predictors of mortality from this jeopardize disease among under-five children. Methods: A facility based prospective cohort study was conducted from November 1/2021 to October 31/2022 at Debre Tabor comprehensive specialized hospital. All under-five children with SCAP adimitted during study period were included. Participants were selected using systematic sampling technique. The collected data were coded, edited and entered into epi-data version 4.2 and then exported to STATA version 17 for further analysis. The Kaplan Meier failure estimate with log-rank test was employed to determine the survival estimates. Cox-proportional hazard regression model was fitted to identify significant variables. Results: The overall incidence density rate of mortality was 5.7 /1000 child- days with median hospital stay 8.2 days. Heart disease (AHR: 4.37; 95%CI: 1.68-11.32), previous admission of SCAP (AHR: 3.87; 95% CI: 1.31-11.43), WFL<-3Z score (AHR: 3.57; 95% CI: 1.02-12.42), impaired consciousness level at admission 3.41(1.14-10.19) and plural effusion (AHR: 3.42; 95%CI: 1.18-9.93) were significant predictors of mortality. Conclusion: In this study, the survival probability of children with SCAP was low. Children with heart disease, previous admission of SCAP, WFL<-3Z score, impaired consciousness level at admission and plural effusion had low survival. Therefore, much emphasis is needed to children with SCAP particularly those with identified predictors.